2022
DOI: 10.1111/josi.12509
|View full text |Cite
|
Sign up to set email alerts
|

Work from home and parenting: Examining the role of work‐family conflict and gender during the COVID‐19 pandemic

Abstract: Many employers introduced or expanded working from home (WFH) in response to increasing infection rates after the onset of the COVID‐19 pandemic. Whether WFH enhances or depletes parents’ resources for their children is still an open question. Drawing on contextual models of parenting and demands‐resources approaches, we examine how WFH during the early stages of the COVID‐19 pandemic was linked to changes in responsive and harsh parenting, particularly in light of pandemic‐related increases in work‐to‐family … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 161 publications
(312 reference statements)
0
18
1
Order By: Relevance
“…Bernhardt et al. (2022) found that essential work was also associated with greater work‐family conflict. Some parents, like Maria, who works as a therapist at a nursing home and whose husband is a construction worker, did what we call a sequential shift rather than a simultaneous shift like those working from home (Harrington Meyer & Abdul‐Malak, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Bernhardt et al. (2022) found that essential work was also associated with greater work‐family conflict. Some parents, like Maria, who works as a therapist at a nursing home and whose husband is a construction worker, did what we call a sequential shift rather than a simultaneous shift like those working from home (Harrington Meyer & Abdul‐Malak, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Semi-structured interviews with mothers illustrated how the pandemic impacted essential workers that mothers who worked outside of the home during the global health crisis were forced to work sequential shifts, returning from their jobs to fulfill the role of helping children with their schoolwork that was now being done within their homes (Lutz et al, 2023). As mentioned by Bernhardt et al (2022), women who worked within the home did see some benefit from not having to work sequential shifts; however, both of these investigations illustrated the intense strain of mothers working simultaneous shifts, juggling working and childcare in the same time period and space. The qualitative nature of Lutz et al's (2023) work provided a platform for mothers of color to express the intense pressures of protecting children from racial discrimination during the pandemic and how that related to decisions they were making about school options.…”
Section: School Changes Impact Mothersmentioning
confidence: 99%
“…Caring for children and household chores are also often enacted by women, and healthy older family members were no longer able to support women in these responsibilities. Increased eldercare demands and decreased childcare support set the stage for empirical findings in this Special Issue that women experienced increased work versus family role conflict and burdens of household and childcare responsibilities (e.g., Bernhardt et al., 2022; Coyle et al., 2023; Dinella et al., 2023; Lee et al., 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Mothers’ increased stress during COVID lockdown has been associated with more harsh parenting and less parent‐child closeness (Chung et al., 2022), along with greater parent anxiety, and lower parenting and co‐parenting quality (Feinberg et al., 2022). Although working from home during COVID was found to be a buffer against increasing harsh parenting (Bernhardt et al., 2022). Mothers who reported higher levels of childcare burden also reported more depression and anxiety, which predicted increased conflict with children (Russell et al., 2020).…”
Section: Introductionmentioning
confidence: 99%